Accidental subarachnoid position of an epidural catheter - Cunha, Ana Sofia; Nunes Marques, João Filipe (Journal of the Portuguese Society of Anesthesiology, 2021)
Epidural analgesia remains a frequently used technique in all perioperative settings and chronic pain management, though still associated with a variety of complications, including technique failure, spinal hematoma or abcess and inadvertent location/migration of the catheter to the intravascular/subdural/subarachnoid space, with potential letal consequences. In this clinical case we report a migration of an epidural catheter intended for chronic pain management, which was placed intrathecally with position confirmed by radiocontrast dye. The authors pretend to highlight with this case that a high suspicion level is crucial for the correct diagnosis of catheter malposition and appropriate management. In our current knowledge, there are no previous published images on the literature showing simultaneous radiocontrast in both the epidural and intratechal space, giving our imagens its singularity.